Una mirada cualitativa sobre la autoevaluación institucional desde la praxis universitaria - Florez-Nisperuza, Elvira Patricia; Hoyos-Merlano, Alina María (Revista Científica, 2020)
This article shows the partial results of a qualitative research carried out in the Department of Natural Sciences of the University of Córdoba, Colombia, related to the characterization of evaluative practices from the reflection of the processes of Self-evaluation, Institutional Evaluation, and Accreditation, with the participation of the students of the X semester and were from a documentary review, it was possible to categorize the self-evaluation as the starting point and permanent exercise to keep the gaze on the university processes and respond with the quality in the alma mater. Evaluative practices in general, nationally and internationally reveal a degree of acceptance to the point of issuing around the concepts, voices within the pedagogical language or the educational context such as: process, quality, reflection, culture, participation; what shows an approach and acceptance of the university atmosphere with the evaluation processes, considering then the university as a unit that generates confidence in the framework of the evaluation, for what should be these the calls then to guide the educational Institutions in Colombia to face these qualification practices in a different way than at present is lived in the school and allowing the teacher information, to conduct himself under this paradigm that must be culture, the culture of the evaluation.